(untitled) (Global Journal of Human-Social Science, 2021)
The chemistry chief examiner of the West African Examination Council has complaint a lot about the weak performance of students on organic chemistry including functional group detection The study therefore investigated whether senior high school teachers who teach chemical concepts to students also demonstrated conceptual difficulties on functional group detection under organic qualitative analysis The study adopted convergent mixed methods procedures to collect both quantitative and qualitative data from 47 chemistry teachers The 47 teachers were sampled through multistage sampling procedures to respond to the Organic Qualitative Analysis Diagnostic Test for Teachers The quantitative data was analyzed using means standard deviations and percentages to reflect no scientific understanding partial scientific understanding and scientific understanding of functional group detection The qualitative data was open-coded and constantly compared to established teachers alternative conceptions and factual difficulties on functional group detection